Research on Bibliometric Analysis of Toulmin's Argument Pattern (TAP) in Learning Physics in the Last Ten Years - Setyo Admoko; Kiki Lutfiah Arizah; Nadi Suprapto; Utama Alan Deta; Suliyanah Suliyanah; Eko Hariyono; Madlazim Madlazim; Rizki Fitri Rahima Uulaa; Mohammad Walid Rasuliy; Yuli Sutoto Nugroho (Indonesia Emerging Literacy Education, 2023)
Objective: Toulmin's Argument Pattern (TAP) is the most widely used argumentation pattern and was first used in science education. TAP has a significant contribution as literature in explaining the concept of argumentation. This study aims to identify the contribution and describe the research profile of applying TAP in physics education during the last ten years. Method: The method used in this research is a bibliometric analysis based on Scopus data with the help of MS Excel and VOSviewer. The results of this study obtained 67 documents related to TAP. Results: Based on the results of bibliometric data visualization related to TAP, 4 clusters (1) discuss TAP focused on learning processes and activities in the classroom. (2) the application of TAP focused on assessing argumentation and critical thinking skills (3) TAP was associated with the identification of the components of scientific argumentation (4) TAP related to contextual problem-solving in improving scientific literacy. Novelty: Physics is the subject that appears the most in research related to the use of TAP, among other science subjects. Based on the results of this study, TAP has several contributions to physics learning in improving students' argumentation skills so that it can be an opportunity for further research. That way, the next one will be able to discuss more deeply related to the TAP, which is applied to physics learning to improve argumentation and critical thinking skills.